Macro phenomena vs micro responses. Multiscale approaches in the dynamic relationship between envelope and context - Maria Teresa Lucarelli; Martino Milardi; Mariateresa Mandaglio; Caterina Claudia Musarella (Agathón)
The current scenario, crossed by contrasting flows where emergencies and development trends often coexist and increase gaps, highlights the need to ‘move’ from the change phase to the phase of change. On many fronts, it is evident that this need is determining an acceleration towards a transformation that has concrete Renaissance characteristics. An example is the use of the ‘multiscalar vision’ in research as a useful criterion for understanding phenomena, both material and immaterial. The contribution addresses the relationships between buildings and their contexts, assuming at the macro scale the stresses that phenomena, such as climate, ‘impose’ on the envelopes and, at the micro scale, the new qualitative and performance responses of envelope systems – innovative and not – that today characterize the panorama of contemporary architecture.